2018
DOI: 10.1186/s12859-018-2510-x
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput cancer hypothesis testing with an integrated PhysiCell-EMEWS workflow

Abstract: BackgroundCancer is a complex, multiscale dynamical system, with interactions between tumor cells and non-cancerous host systems. Therapies act on this combined cancer-host system, sometimes with unexpected results. Systematic investigation of mechanistic computational models can augment traditional laboratory and clinical studies, helping identify the factors driving a treatment’s success or failure. However, given the uncertainties regarding the underlying biology, these multiscale computational models can t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 55 publications
0
75
0
Order By: Relevance
“…Population dynamics of tumours have been further studied by Gonzales-Garcia et al (2002) and Sole (2003) who concluded through agent-based modelling that spatial genetic heterogeneity observed in tumours naturally follows from simple ecological competitor dynamics. Since then, many multi-agent models of tumour growth with increasing physical accuracy have been proposed (Abbott et al 2006, Zhang et al 2009, Bentley 2013, Ozik et al 2018. Yet, few of these approaches take into account the dynamics of and interaction with the tumour environment, particularly host tissue, immune system, and boundary conditions imposed by anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Population dynamics of tumours have been further studied by Gonzales-Garcia et al (2002) and Sole (2003) who concluded through agent-based modelling that spatial genetic heterogeneity observed in tumours naturally follows from simple ecological competitor dynamics. Since then, many multi-agent models of tumour growth with increasing physical accuracy have been proposed (Abbott et al 2006, Zhang et al 2009, Bentley 2013, Ozik et al 2018. Yet, few of these approaches take into account the dynamics of and interaction with the tumour environment, particularly host tissue, immune system, and boundary conditions imposed by anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches, however, neglect the complex interactions in the evolving multi-level networks of normal and diseased tissues [35]. Targeted interventions do not only affect just single cell types; biochemical and biophysical feedbacks-combined with intercellular heterogeneity and natural selection [32] and amplified by physical constraints [36]-can cause secondary effects such as therapeutic resistance (e.g., by selecting for resistant cancer clones), worsened drug delivery, and treatment toxicity [6,32,37]. Thus, next-generation therapies must not just treat single cell types, but rather steer the multicellular systems towards balance.…”
Section: Research Group Contextmentioning
confidence: 99%
“…In particular, computational modeling approaches, which include both mathematical modeling of complex cell and molecular systems and statistical modeling of large datasets, are a powerful vehicle for synthesizing disparate and sometimes conflicting data into an integrated biological understanding. Ideally, computational modeling approaches work recursively with experimental workflows; mathematical models quantitate and formalize the largely qualitative, observation-driven "mental models", and the iterative comparison of model outputs to experimental data informs model refinement and also suggests new experimental directions [6][7][8][9].The use of mathematical models clarifies the biological conditions or parameters under which the "mental model" can explain the experimental and simulation data. Increasingly, statistical modeling approaches including machine learning and bioinformatics are used to complement mathematical modeling of cell and molecular biological systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…This began the design of cell-cell interaction rules to create a multicellular cargo delivery system that actively delivers a cancer therapeutic beyond regular drug transport limits to hypoxic cancer regions. These model rules were manually tuned to achieve this (as yet unoptimised) design objective, requiring weeks of people-hours to configure, code, test, visualise, and evaluate (Ozik et al, 2018). Ghaffarizadeh et al (2018) also presented 3-D simulations of cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The results provided insights into therapeutic failure, thus demonstrating the potential of high-throughput computing to investigate high dimensional cancer simulator parameter spaces. High-throughput model investigation and hypothesis testing provides a new paradigm for solving complex problems, gaining new insights, and improving cancer treatment strategies (Ozik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%